ANTIBIOTIC-ASSOCIATED DIARRHEA IN CHILDREN: PRINCIPLES OF PROPHYLAXIS AND TREATMENT - V. V. Chernikov; Andrei Nikolaevich Surkov ("Paediatrician" Publishers LLC, 2012)
Antibacterial treatment has wide usage in modern practical medicine, as it allows achieve rapid positive effect in treatment of infectious diseases. However it is necessary to remember, that various side-effects are not rare during antibacterial therapy. One of the main side-effects is intestinal microflora disturbances, including antibiotic-associated diarrhea. That is why it is so important to understand the principles of its prophylaxis and treatment. The fundamental knowledge about normal intestinal microflora and its functions, epidemiology, pathogenesis, clinical presentation, diagnostics, treatment and prophylaxis of antibiotic-associated diarrhea in children are reviewed in this study.